2021
DOI: 10.18178/ijiet.2021.11.5.1516
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Training Course Using Synchronous Conferencing Tools for Hospitality and Tourism Education in Vietnam: A Constructivist Approach

Abstract: Despite its significant damage to the hospitality and tourism industry, the pandemic of COVID-19 indeed has reinforced the needs for not only the hospitality and tourism education, but also the whole educational system of Vietnam, to make use of technological innovations in education, among which synchronous conferencing tools are currently utilized for changing their mode from physical classroom to online learning. This study adopts the constructivist approaches to propose a training course designed to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The teacher training program proposed herein was designed to translate the three constructivist approaches of "knowledge is constructed by learners," "knowledge is based on experience" and "a strong class community is essential" (Kosnik et al, 2018, p. 105) into specific pedagogical practices. In our previous study (Luong and Kim, 2021), we selected and designed different types of learning activities (Table 5) for teachers to help them acquire the complex skills required for synchronous online teaching (Table 2).…”
Section: Course Design and Content 41 A Conceptual Model For The Prop...mentioning
confidence: 99%
See 1 more Smart Citation
“…The teacher training program proposed herein was designed to translate the three constructivist approaches of "knowledge is constructed by learners," "knowledge is based on experience" and "a strong class community is essential" (Kosnik et al, 2018, p. 105) into specific pedagogical practices. In our previous study (Luong and Kim, 2021), we selected and designed different types of learning activities (Table 5) for teachers to help them acquire the complex skills required for synchronous online teaching (Table 2).…”
Section: Course Design and Content 41 A Conceptual Model For The Prop...mentioning
confidence: 99%
“…On the basis of the current literature and textbooks that provide guidelines on synchronous online teaching, our previous study (Luong and Kim, 2021) identified the complex skills needed to facilitate synchronous online classes. These include developing online presence , planning lessons , handling technology , adapting to learners’ preferences and classroom management .…”
Section: Related Workmentioning
confidence: 99%